Evaluation of esterification routes for long chain cellulose esters. Issue 11 (November 2019) - Willberg-Keyriläinen, Pia; Ropponen, Jarmo
Abstract: Long chain cellulose esters are internally plasticized bio-based materials, which have good future potential in several applications such as coatings, films and plastics. The long chain cellulose esters with different side chain lengths were synthesized using different esterification methods. When homogeneous esterification was used, the acyl chloride method was the most effective esterification method and cellulose esters prepared using this method have the highest degree of substitution values (DS). In this case, the long chain cellulose esters showed DS values from 0.3 to 1.3 depending on the side chain length of cellulose esters. CDI activation, vinyl transesterification and anhydride routes resulted in somewhat lower DS values. The cellulose was also pretreated with ozone, which decreased cellulose molar mass, and resulted in synthesized cellulose esters having higher DS and better reaction efficiency than untreated cellulose. When heterogeneous esterifications were used, only acyl chloride method seemed to work. Abstract : Materials chemistry; Cellulose; Esterification; Long chain cellulose ester